ROLE PLAY IN VIDEO TO ACCELERATE NON-ENGLISH STUDENTS’ MASTERY OF SPEAKING COMPETENCE - Asna Usman Dilo; La Aba (Al-Lisan: Jurnal Bahasa, 2019)
To teach English to non-English major students in Islamic University is unique. This perception is also applied among lecturers and to stimulate a conversation situation in which students might find and give them an opportunity to practice and develop their speaking ability. Therefore, the use of role play that involved in short film documenter or video is used in this study to make their English creatively, not only to practice speaking ability but the students can explore their acting. This study is an action research study, where pre-test and posttest are administered to obtain the data, in addition to observation and literature study. This research is carried out in two cycles, every cycle there are four components they are: planning, acting, observing, and reflecting. The result of this research showed that used role play in video can accelerate the non-English students’ department mastery of speaking competence. It showed the first cycle showed that only 10 or 40% students were competent. While in the second cycle, there were 25 or 88% students gained the score more than 80. It means that the indicator of success has reached. Keywords: Role Play in Video, Speaking Competence, Non-English Students